More money, more problems? An examination of the dynamic relationship between income and work–family conflict. Issue 2 (14th March 2022) - Rubenstein, Alex L.; Morrison, Hayley M.; Whiting, Steven W.; Bosco, Frank A.
Abstract : Income from regular employment is a primary means by which individuals support themselves. Yet, little research has examined how making more money over time relates to employees' ability to simultaneously manage work and family role obligations. Drawing from resource allocation theory, in two studies we examined the dynamic relationship between income and work–family conflict (WFC). We hypothesized that income trends would positively predict WFC trends, as making more money could demand employees devote greater resources to their work role, depleting remaining resources to devote to family. In Study 1, with data from a large sample surveyed over 4 years, we found that income trends were positively associated with WFC trends. Further, this relationship was more accentuated for women than men. In Study 2, we sought to replicate and extend the Study 1 findings by modelling theoretical mechanisms that could account for the positive dynamic income–WFC relationship. We again found a positive relationship, although the income–gender interaction failed to replicate. Mediation analyses revealed increased investments of the self into work explained the link between increased income and increased WFC, compared to other mechanisms. As a whole, in terms of WFC, more money earned ultimately conferred more, not less, problems for employees. Practitioner points: Our findings suggest that income changes over time positively predict work–family conflict changes over time. Although pay is of course a significant motivator of desired work behaviour, our results highlight some of the peripheral consequences that might result as employees make more money. Our research suggests this dynamic relationship is best explained by employees' increased investments of the self into work, and therefore concerns a need for well‐paid employees to think more about how they balance work and family goals. In one of two samples, the positive income–WFC dynamic relationship was stronger for women than for men, highlighting not only that making more money can increase WFC over time but also for whom it is more likely to do so.